Uji Aktivitas Antiinflamasi In Vitro Etlingera elatior (Jack) R.M. Smith dengan Metode Stabilisasi Membran Sel Darah Merah - Adryan Fristiohady; Wahyuni Wahyuni; Fadhliyah Malik; Nurjeddah Fariane; Muhammad Ilyas Y.; Mentarry Bafadal; Sahidin F. (Fakultas Farmasi Universitas Pancasila, 2020)
Wualae (Etlingera elatior (Jack) R. M. Smith) is plant that traditionally used as traditional medicine in Southeast Sulawesi. It contains fl avonoids, tannins, and terpenoids that act as anti-infl ammatory. The studyaims to investigate the anti-infl ammatory activity of ethanolic extract of wualae by stabilizing human red bloodcell (HRBC) membrane. Hemolysis and stability due to oxidative induction and hypotonic solutes are used asmeasures of anti-infl ammatory activity. The positive controls used in this study were diclofenac sodium withvarious concentrations of 250 ppm; 500 ppm; 750 ppm; 1000 ppm; 1250 ppm; and 1500 ppm. Sample wasalso having similar identical concentration. According to the results of stability and hemolysis percentage ofE. elatior fruit ethanol extract to HRBC were 57,75% and 42,25% (250 ppm), 66,71% and 33,29% (500 ppm),74,10% and 25,90% (750 ppm), 75,72% and 24,28% (1000 ppm), 79,87% and 20,13% (1250 ppm), and 84,89%and 15,11% (1500 ppm). Compared with diclofenac sodium stability and hemolysis percentage were 62,61%and 37,39% (250 ppm), 66,71% and 33,29% (500 ppm), 71,02% and 28,98% (750 ppm), 72,10% and 27,90%(1000 ppm), 73,94% and 26,06% (1250 ppm), 76,63% and 23,37% (1500 ppm). These data suggest that the ethanolic extract of wualae is potentially have activity as anti-infl ammatory.